Holistic influence on contemporary jazz vocal improvisation with reference to the works of Gloria Cooper and Kitty Margolis. - Bauer, Lisa (College of Music, 2014)
Through the analysis of aspects such as experience, vocal expression, improvisatory techniques and teaching approach of two jazz vocalists from different social, educational and musical backgrounds in the United States of America, the hope is to achieve a greater understanding of and confirm the factors which play important roles in the vocalist's improvement of effective, authentic jazz improvisation. The focus is on the effect which experience, mentors and musical training have on the two vocalists' approach to teaching and performing jazz styles. This study also investigates the possibility that emotional, educational and physiological factors holistically influence the contemporary jazz vocalist's experience of using the body as a medium of expression via production of sound from the vocal chords.